Relationship between performance appraisal politics and job satisfaction :does distributive justice act as a mediating role? - Awangku, Mohamad Najib. (Universiti Malaysia Sarawak, UNIMAS, 2007)
The study was conducted to examine the mediating role of distributive justice in the relationship between performance appraisal politics and job satisfaction. This study used a sample of 150 usable questionnaires that were gathered from employees who have worked in the management and non-management level in Pejabat Pos Malaysia Berhad, Sarawak.Outcomes of stepwise regression analysis showed that the inclusion of distributive justice into analysis had increased effect of performance appraisal politics (i.e., motivational motive and punishment motive) on job satisfaction. This result demonstrates that distributive just ice does act as a full mediator in the performance appraisal practices of the organization. In addition, implications of this study to performance appraisal practice and theory, methodological and conceptual limitations, as well as directions for future research, are discussed.